2016
DOI: 10.1098/rsos.160350
|View full text |Cite
|
Sign up to set email alerts
|

Two species of Southeast Asian cats in the genus Catopuma with diverging histories: an island endemic forest specialist and a widespread habitat generalist

Abstract: Background. The bay cat Catopuma badia is endemic to Borneo, whereas its sister species the Asian golden cat Catopuma temminckii is distributed from the Himalayas and southern China through Indochina, Peninsular Malaysia and Sumatra. Based on morphological data, up to five subspecies of the Asian golden cat have been recognized, but a taxonomic assessment, including molecular data and morphological characters, is still lacking. Results. We combined molecular data (whole mitochondrial genomes), morphological da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…This divergence estimate is supported by previous molecular studies and found that the genus Axis separated from the Cervus clade during the Late Pliocene 23 , 30 . During the Late Pliocene, numerous species split due to the various climatic and geographical changes that acted as a driver of speciation in Southeast Asia, e.g., Muntiacus 31 ; the Asian golden cat and the bay cat 32 ; C. perrieri and C. cusanus 33 ; and Macaca species 34 . The Bayesian skyline plot analysis strongly indicates that the hog deer population has been demographically stable over the last 8000–40,000 years and also provides evidence of a slight reduction in the effective population size over the last ~800–5000 years BP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This divergence estimate is supported by previous molecular studies and found that the genus Axis separated from the Cervus clade during the Late Pliocene 23 , 30 . During the Late Pliocene, numerous species split due to the various climatic and geographical changes that acted as a driver of speciation in Southeast Asia, e.g., Muntiacus 31 ; the Asian golden cat and the bay cat 32 ; C. perrieri and C. cusanus 33 ; and Macaca species 34 . The Bayesian skyline plot analysis strongly indicates that the hog deer population has been demographically stable over the last 8000–40,000 years and also provides evidence of a slight reduction in the effective population size over the last ~800–5000 years BP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Disappearance of the corridor and expansion of the modern rainforest was proposed to have led to extinction or range reduction of many of its former travellers 4 . Conversely, it is also associated with population expansion of rainforest species such as the Bornean orangutan and the Asian golden cat 12,13 . Given the emerging cosmopolitan nature of Pleistocene Southeast Asia, testing this hypothesis will make a major contribution to global understandings of how hominin taxa had different ecological tolerances or capacities 18 and the role of climate change in driving megafaunal extinctions 19 .…”
Section: Main Textmentioning
confidence: 99%
“…and C.R. using overlapping PCR products using long-range PCR ( Additional file 1c ) followed by library construction and MiSeq sequencing, or Sanger sequencing as described in Patel, Förster, and Kitchener (2016) [ 6 ] and Liedigk et al. (2015), Roos et al.…”
Section: Data Validation and Quality Controlmentioning
confidence: 99%